Resilience of agricultural systems: biodiversity-based systems are stable, while intensified ones are resistant and high-yielding - Dardonville, M.; Bockstaller, C.; Villerd, J.; Therond, O.
New types of farming systems have emerged in response to societal demands to reduce environmental impacts and dependence on non-renewable resources. These agriculture models can be classified according to their relative use of anthropic inputs or biodiversity and associated ecosystem services as agricultural production factors. All these models are exposed to climate change, price volatility and other disturbances. However, little is known about their resilience levels and the factors that drive them.
Keywords: ECOSYSTEM SERVICES; NATURAL CAPITAL; STABILITY; RESISTANCE; CROPPING SYSTEM